Primary Cutaneous CD30+ Anaplastic Large T Cell Lymphoma in a Patient Treated with Cyclosporine for Actinic Reticuloid - T. Gambichler; N. Patsinakidis; L. Susok; M. H. Segert; M. Doerler (Case Reports in Dermatological Medicine)
Actinic reticuloid (AR)—a subtype of chronic actinic dermatitis—clinically and histopathologically shows lymphoma-like features. We report a male patient initially diagnosed with erythrodermic cutaneous T cell lymphoma (CTCL) who developed severe broadband photosensitivity. Clinical evaluation, histopathology, and phototesting were consistent with AR. The patient was treated with cyclosporine 150–300 mg/d. Under this therapy, he developed several times primary cutaneous anaplastic large cell lymphomas (C-ALCL) which in part tended to regress spontaneously under cyclosporine reduction. The association between cyclosporine treatment and development of C-ALCL and other CD30+ lymphoproliferative disorders has previously been reported in patients with atopic dermatitis, psoriasis, and transplant patients. In conclusion, the present case highlights the difficulties arising in the distinction between AR and CTCL and shows that long-term cyclosporine treatment may cause C-ALCL development in AR as well.